The PHANGS-AstroSat atlas of nearby star-forming galaxies - Hassani, Hamid; Rosolowsky, Erik; Koch, Eric W.; Postma, Joseph; Nofech, Joseph; Corbould, Harrisen; Thilker, David; Leroy, Adam K.; Schinnerer, Eva; Belfiore, Francesco; Bigiel, Frank; Boquien, Médéric; et al. (The astrophysical journal. Supplement series, 2024)
We present the Physics at High Angular resolution in Nearby GalaxieS (PHANGS)-AstroSat atlas, which contains UV imaging of 31 nearby star-forming galaxies captured by the Ultraviolet Imaging Telescope on the AstroSat satellite. The atlas provides a homogeneous data set of far-UV and near-UV maps of galaxies within a distance of 22 Mpc and a median angular resolution of 1.″4 (corresponding to a physical scale between 25 and 160 pc). After subtracting a uniform UV background and accounting for Milky Way extinction, we compare our estimated flux densities to GALEX observations, finding good agreement. We find candidate extended UV disks around the galaxies NGC 6744 and IC 5332. We present the first statistical measurements of the clumping of the UV emission and compare it to the clumping of molecular gas traced with the Atacama Large Millimeter/submillimeter Array (ALMA). We find that bars and spiral arms exhibit the highest degree of clumping, and the molecular gas is even more clumped than the far-UV (FUV) emission in galaxies. We investigate the variation of the ratio of observed FUV to Hα in different galactic environments and kiloparsec-sized apertures. We report that ∼65% of the variation of the log10(FUV/Hα) can be described through a combination of dust attenuation with star formation history parameters. The PHANGS-AstroSat atlas enhances the multiwavelength coverage of our sample, offering a detailed perspective on star formation. When integrated with PHANGS data sets from ALMA, the Very Large Telescope-MUSE, the Hubble Space Telescope, and JWST, it develops our comprehensive understanding of attenuation curves and dust attenuation in star-forming galaxies.